The Influence of Different Parameters on the Electro Refining of Copper (The International Journal of Engineering & Information Technology (IJEIT), 2024)
The experiments were performed using the acidic electrolyte composed of copper sulphate and sulphuric acid. The electro refining process was carried out at the temperatures of 40, 50, and 650C. On the basis of the experiments performed it was stated that the temperature of the electrolyte has significant influence on the copper consumption as well as the topography of copper deposited on the cathode. The influence of the temperature was explained by the increase in copper sulphate solubility and acceleration of the ions diffusion in the adjacent to the electrodes layer, which in consequence lead to the decrease in the resistances of Cu2+ ions deposition.It was also stated that increase in the current density beside the increase in the production rate causes the decrease in the current efficiency. The addition of gelatin to an electrolyte causes the smoothing the cathode deposit but increase in power consumption consequence of the increasing the resistances of Cu2+ ions deposition and as a result of it the increase in the cell voltage. The topography of the cathode deposit was observed using a metallurgical microscope. It was concluded that the optimum conditions for copper electro refining are: the consumption of the electrolyte- 50 kg Cu/m3, 200 kg H2SO4/m3 and gelatin-10 ppm, the temperature - 650C, current density-250A/m2.